2016
DOI: 10.1016/j.ces.2016.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the hydrodynamic behaviour of slug flow in a horizontal pipe

Abstract: Abstract:Despite the research efforts in the last decades, the dynamic behaviour of gas-liquid two-phase flows remains a challenging topic. This is due to the growing demand within the petroleum, process and nuclear industries. In particular, data on the behaviour of these flows in more industry relevant fluids are limited. This paper presents a summary of the experimental results on the hydrodynamic behaviour of slug flow using airsilicone oil mixture in a horizontal 67 mm internal diameter pipeline. A series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(6 citation statements)
references
References 45 publications
3
3
0
Order By: Relevance
“…The frequency of slugs has been commonly correlated in term of pipe diameter and liquid superficial velocity, where a neglected change with axial position is suggested. This work ,in accordance with to Fossa et al (2003), [10] and [11], indicates the frequency seems to be better correlated in term of Strouhal number as a function of liquid volume fraction. However, this approach needs to be tested against a wide range of experimental data before a final conclusion can be reached.…”
Section: Slug Frequencysupporting
confidence: 85%
See 1 more Smart Citation
“…The frequency of slugs has been commonly correlated in term of pipe diameter and liquid superficial velocity, where a neglected change with axial position is suggested. This work ,in accordance with to Fossa et al (2003), [10] and [11], indicates the frequency seems to be better correlated in term of Strouhal number as a function of liquid volume fraction. However, this approach needs to be tested against a wide range of experimental data before a final conclusion can be reached.…”
Section: Slug Frequencysupporting
confidence: 85%
“…7 shows a satisfactory agreement between the experimental results and the correlation of Fossa et al and eq. (1), similar findings are reported by [10] and [11]. The frequency of slugs has been commonly correlated in term of pipe diameter and liquid superficial velocity, where a neglected change with axial position is suggested.…”
Section: Slug Frequencysupporting
confidence: 80%
“…Thaker and Banerjee (2015) 2017)). Abdulkadir et al (2016) found that the slug frequency data obtained in a 67 mm ID pipe with a mixture of air and silicone oil, can be well correlated using a gas based Strouhal number StG = ! " " ⁄ # and liquid volume fraction λL $ = " " + " ⁄ #.…”
Section: Nomenclaturementioning
confidence: 98%
“…A further way of analysing slug structural effects, is through the comparison of slug front and tail velocities. As pointed out by Abdulkadir et al [34], relatively close values of slug front and tail velocity can be used as an indication of good flow development. Therefore, by categorising the different slug structures within a developed flow, the variation present for the different structures can be used as an indication of their stability, or degree of representation.…”
Section: Behaviour Of Slug Fronts and Tailsmentioning
confidence: 93%